REGISTRATION FIDUCIARY GUARANTEE REALIZE LEGAL PROTECTION OF CREDITORS AND DEBTOR - Ansharullah Ida; Gunarto Gunarto; Jelly Leviza (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In Article 11 of the Law of Fiduciary determined that the object is in the territory of the Republic of Indonesia or outside the territory of the Republic of Indonesia. Bound by fiduciary shall be registered at the registration office fiduciary duties within the scope of the Department of Law and Human Rights. Fiduciary guarantee a follow-up agreement set out in the fiduciary deed as collateral for the repayment of certain money. This became the preferred fiduciary guarantee for creditors if the fiduciary is registered in Fiduciary Registration Office. This is because the preferred position is guaranteed for their registration. The imposition of fiduciary must be made by Deed in Indonesian and thus constitute a fiduciary warranty deed. Imposition by fiduciary guarantee are then required to be registered in Fiduciary Registration Office. The obligation is in terms of the binding fiduciary and fiduciary registration so that the object of the guarantee that has the power of binding and has the same executorial court decision. Keywords: Fiduciary and Legal Protection.